2007
DOI: 10.1016/j.rser.2005.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Social barriers in wind power implementation in The Netherlands: Perceptions of wind power entrepreneurs and local civil servants of institutional and social conditions in realizing wind power projects

Abstract: The primary social factors for the implementation of wind energy projects in a liberalized market are entrepreneurs willing to invest. Understanding conditions that trigger entrepreneurs to invest in these projects, and understanding conditions that determine the chance of success for entrepreneurs to implement and exploit their projects, is vital for setting up effective policies to stimulate wind electricity generation. This paper analyses the way in which wind power entrepreneurs and local civil servants ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…A large number of studies have shown that the most important argument against wind power is the visual impact on the landscape (Agterbosch et al, 2007;Pasqualetti, 2000;Toke, 2005;Toke et al, 2008;Wolsink, 2007). Other factors include noise and shadows, landscape intrusion, environmental concerns and decreased value of neighbouring properties (see Table 1).…”
Section: Wind Power Planning In Previous Literature: An Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…A large number of studies have shown that the most important argument against wind power is the visual impact on the landscape (Agterbosch et al, 2007;Pasqualetti, 2000;Toke, 2005;Toke et al, 2008;Wolsink, 2007). Other factors include noise and shadows, landscape intrusion, environmental concerns and decreased value of neighbouring properties (see Table 1).…”
Section: Wind Power Planning In Previous Literature: An Overviewmentioning
confidence: 99%
“…Devine-Wright, 2005;Gross, 2007;Wüsterhagen et al, 2007) and suggest that the implementation of open and "collaborative" decisionmaking processes involving different stakeholders will result in less public opposition (Breukers and Wolsink, 2007;Wolsink, 2007;Wüsterhagen et al, 2007). Agterbosch et al, 2007;Coles and Taylor, 1993;DevineWright, 2005;Jobert et al, 2007;Johansson & Laike, 2007;Kellett, 2003, Pasqualetti, 2000Strachan & Lal, 2004, Toke et al, 2008Wolsink, 2000;Woods, 2003  Noice and shadows Agterbosch et al, 2007;Coles and Taylor, 1993;DevineWright, 2005;Strachan & Lal, 2004;Toke et al, 2008;Wolsink, 2000;Woods, 2003  Landscape intrusion (decreased value of natural and cultural landscape) Breukers & Wolsink, 2007;Coles and Taylor, 1993;Devine-Wright, 2005;Johansson & Laike, 2007;Toke et al, 2008;Woods, 2003  Environmental concerns (impact on wildlife, vegetation and soil etc.) Agterbosch et al, 2007;Coles and Taylor, 1993;Strachan & Lal, 2004;Toke et al, 2008;Wolsink, 2000;Woods, 2003  Decreased property values Agterbosch et al, 2007;Coles and Taylor, 1993;…”
Section: Wind Power Planning In Previous Literature: An Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…His [24] studies pointed out that the level of participation of the public, and responses to public opinion were key factors which affected the future development of wind energy. In a 2007 study Agterbosch et al [33] pointed out that public opinion would still influence the outcome of wind energy development, even though the local government has the authority to make the final decision. That is, public awareness and participation in the development of RE can significantly impact a country's future development of its wind energy.…”
Section: Introductionmentioning
confidence: 99%